International Visiting Scholars: Brain-Circulation and Internationalization - Shimmi, Yukiko (International Higher Education, 2014)
International visiting scholars who temporarily visit universities in different countries for academic purposes are an important group of people in the era of globalization. However, they have not received much attention in studies or practices. In this article, the definitions and trends of international visiting scholars, their flexible status, and the importance of this population from the perspectives of brain-circulation and internationalization of higher education are discussed.